Revision of the genus Eueupithecia Prout, 1910 from Argentina (Lepidoptera, Geometridae, Sterrhinae) - Hausmann, Axel; Heard, Tim A.; Kay, Fernando Mc; Raghu, S. (Zootaxa, 2016)
A new species is described from Argentina: Eueupithecia vollonoides sp. n. and a differential diagnosis from E. cisplatensis Prout, 1910 is given. The genus Eueupithecia Prout, 1910 (Sterrhinae), so far having been retained to be monotypic, includes two species now.